Checkpoint Inhibitor-Associated Autoimmune Diabetes Mellitus: A Case Report - Gnanapragasam, Helen Prathiba (J Endocr Soc, 2021)
Introduction: Checkpoint Inhibitors have revolutionized the management in oncology by stimulating the immunological response to cancer. On the contrary, there is an increase in immune-related adverse effects affecting various systems including the endocrine. We report a unique case of new-onset diabetes with diabetic ketoacidosis (DKA) within 18 days of receiving checkpoint inhibitors for Merkel Cell Carcinoma. Clinical Case: An 86-year-old man diagnosed with locally advanced Merkel cell carcinoma underwent surgery and radiotherapy to his right face and neck. Four months later, the positron emission tomography (PET) scan was consistent with liver metastasis. Pembrolizumab, a programmed death receptor-1 (PD-1) inhibitor was initiated as next line treatment. Prior to starting pembrolizumab, his blood glucose was 92 mg/dL (60–120) with no previous history of diabetes mellitus. He presented 18 days later to the emergency room with altered mental status, polyuria, and polydipsia with a blood glucose of 980 mg/dL, anion gap of 26 mmol/L (5–15), and was managed for DKA with new-onset Diabetes Mellitus. HbA1C was 7.0% (4–5.6). He was discharged on subcutaneous insulin glargine once daily, pre-meals insulin aspart, and was referred to the endocrinology clinic. Further investigations obtained during the clinic visit demonstrated low C-peptide of <0.7 ng/mL (0.8–6), glucose 76 mg/dL, positive glutamic acid decarboxylase (GAD-65) antibodies of >25,000 nmol/mL (<0.02), negative islet antigen-2 antibody, islet cell antibody and zinc transporter 8 antibodies. Other endocrine tests showed normal thyroid function, cortisol, and adrenocorticotrophic hormone (ACTH) levels. The patient was educated on checkpoint inhibitor-associated autoimmune diabetes and the need for a lifelong insulin regimen. Clinical Lesson: Our case highlights the immune-related adverse effect involving the endocrine system from checkpoint inhibitor therapy. In comparison to the other common endocrinopathies associated with checkpoint inhibitors, autoimmune diabetes is rare (~ 1–2% incidence) and only less than half demonstrate antibodies with a median time of 8 weeks since exposure. GAD-65 antibodies are the commonest antibody noted and our patient had a robust GAD-65 antibody of >25,000 depleting C-peptide within 18 days of receiving the Pembrolizumab resulting in DKA with a new onset of diabetes. We conclude that diabetes mellitus is a rare but serious adverse effect of immune checkpoint inhibitor therapy. Society for Immunotherapy of Cancer Toxicity Management Working Group consensus recommendations from 2017 recommends routine screening to include baseline HbA1c, basic metabolic panel, thyroid function test, AM cortisol, and ACTH prior to treatment. It also recommends repeating the thyroid function test and basic metabolic panel to allow the monitoring of glycemic trends before each cycle.